Factors that influence on audit delay (case study on LQ-45 company listed on the Indonesia Stock Exchange 2016-2019) - Kampono Imam Yulianto (Privietlab, 2021)
This study aims to analyze the effect of company size, KAP size, and profitability on audit delay. The population used is all LQ 45 companies listed on the Indonesia Stock Exchange (IDX) in the 2016 to 2019 period. Sampling was 17 companies. The research method in this study uses descriptive statistical analysis and multiple linear regression analysis with 3 classical assumption tests. The results of this study indicate that the firm size variable has a significant positive effect on audit delay, and the profitability variable has a negative and significant effect on audit delay. Meanwhile, the KAP size variable has no effect on audit delay. Taken together, all variables (firm size, firm size, and profitability) also have an effect on audit delay.